Restorative Justice in the Criminal Justice System: An Alternative Approach to Offenders’ Rehabilitation and Victims’ Recovery - Purwanto, Purwanto; Damayanti, Putri; Faizal, Muhammad; Fawaid, Bahrul (LifeSciFi, 2025)
Restorative justice is an alternative approach in the criminal justice system that balances offender rehabilitation, victim recovery, and community interests. This article analyze the implementation of restorative justice in Indonesia, its contribution to offender rehabilitation, and its role in facilitating victim recovery and strengthening a sense of social justice. The research method used is normative-juridical with descriptive analysis, reviewing laws and regulations, court decisions, academic literature, and international practices as comparative material. The results of the study indicate that restorative principles have been institutionalized through the Juvenile Justice and Child Protection Law, the Criminal Code, Supreme Court Regulation Number 1 of 2024, and regulations related to the termination of prosecution through a peace agreement. Offender rehabilitation is achieved through education, counseling, skills training, mediation, and community involvement to reduce recidivism. A victim-centered approach prioritizes compensation, psychosocial support, and community participation, fostering justice, social reintegration, and local wisdom–based collective harmony. Obstacles such as limited facilities, officer training, inter-agency coordination, and social stigma need to be addressed for effective implementation. Restorative justice affirms the philosophy of humanist criminal law, creating an inclusive, participatory, and recovery-oriented justice system, while strengthening social harmony and public trust in the law.